Komitmen Kerja Pegawai dalam Melaksanakan Tugas di Badan Kepegawaian Daerah Provinsi Sumatera Barat - Muhammad Hasbi Saputra; Elizar Ramli (Universitas Negeri Padang, 2019)
This research is motivated by the observation that there are still employees who have low work commitments at the Regional Civil Service Agency of West Sumatra Province. The formulation of the problem in this study is how high the work commitment of the Regional Personnel Agency of West Sumatra Province in carrying out its duties. This study aims to obtain information about the work commitment of employees of the Regional Civil Service Agency of West Sumatra Province which are seen from aspects of loyalty, involvement, discipline, and attachment. This type of research is descriptive with a population of employees at the Regional Civil Service Agency of West Sumatra Province, amounting to 80 people. This research is a sample research. The sampling technique itself uses the Proportional Stratified Random Sampling technique so that the respondents were 49 people. The research instrument was a questionnaire with a Likert scale model with five alternative answers, namely (SL), (SR), (KD), (JR), and (TP), which had been tested for validity and reliability through trials on 10 respondents in the population but outside of the sample set. This questionnaire is declared valid with rho rhocount> from rhotablewhich is 0,976>0.648 with a confidence level of 95% and reliability is stated reliably with rhocount> from rhotable which is 0,976> 0,648. For research data, it is processed using the mean formula. Based on the results of the study showed that the work commitment of employees of the Regional Personnel Agency of West Sumatra Province in carrying out tasks seen from the aspect of loyalty was in the high category with an average score of 3.70. For aspects of involvement are in the high category with an average score of 3.61. For disciplinary aspects are in the high category with an average score of 3.61. Furthermore, the attachment aspect is in the high category with an average score of 3,71. Overall, the work commitment of employees of the Regional Civil Service Agency of West Sumatra Province in carrying out tasks is in the high category with an average score of 3,66. Based on these results the authors suggest that employee work commitments be maintained and improved again so that they can improve the effectiveness of the work of employees at work.The Key word: Employee work commitment